The evaluation of neural and vascular hyper-reactivity for sensitive skin - Sun, L.; Wang, X.; Zhang, Y.; Wang, T.; Li, X.; Ma, Y. (Skin research and technology, 2016)
Background The impaired barrier function has been studied comprehensively but few about the heighted neural and vascular reaction for the pathogenesis of sensitive skin. Methods Lactic acid stinging test (LAST) was used to identify sensitive subjects in selection phase. In the subsequent test phase, the baseline value of the blood flow (BF) and the current perception threshold (CPT) was measured by non‐invasive instruments firstly. Then, the 0.001% capsaicin was applied to the nasolabial fold for 5 min. After the capsaicin test (CAT), the BF (immediately after the CAT) and CPT (1 h later after the CAT) were measured again. Blood sample were collected for genetic analysis of four TRPV1 gene single nucleotide polymorphisms between the positive‐group and the negative‐group. Result The positive‐group had lower baseline value of CPT at 5 and 250 Hz compared with the negative‐group, but no difference in baseline value of BF. After the CAT, significant variation in CPT at 5 and 250 Hz values and the BF were found in positive‐group but not in negative‐group. The genotype frequencies of AG/GG in RS224534 and AC/CC in RS4790523 in positive‐group were higher than that of negative‐group. Conclusion The sensitive subjects were prone to be stimulated by capsaicin to trigger neural and vascular hyper‐reactivity. The genetic variation of TRPV1 and the unpleasant sensation demonstrate that TRPV1 play an important role in the pathogenesis of sensitive skin. Our study supports that sensory irritation inhibitors and anti‐inflammatory compounds should be considered to be added in cosmetics to reduce the heighted neural and vascular reaction of sensitive skin.